ANALISIS POSTKOLONIAL DALAM NOVEL KEMBALI KE DESA KARYA TRI BUDHI SASTRIO - Yuniani, Emi; Yuwono, Yuwono; Mardiana, Ninik (Universitas Andalas, 2022)
Postcolonial theory is used to examine the novel Back to the Village by Tri Budhi Sastrio. The novel Back to the Village is the story of an innocent village girl named Putu Larasati, a teenager who was snatched away by her youth, then stranded in the Dutch Company barracks and fell into the arms of a Company soldier named Captain Robert van Eyk. This village girl was lucky because the soldier, although at first was a soldier who was a jerk and a hooker, turned out to love her with all her heart and sincerity. The sincerity and loyalty of the soldier who had become her husband was well recorded in the mind of this innocent country girl. Everything becomes beautiful, calm, serene, and peaceful. The method used in this research is descriptive qualitative method using postcolonial theory. The data of this research are excerpts from the description of postcolonial theory in the novel